ROLE OF INDIVIDUALISED HOMOEOPATHIC MEDICINE IN MANAGEMENT OF PSORIASIS: AN EVIDENCED BASED CASE REPORT - Dr. Abhijit Chattopadhyay; Dr. Munjal Thakar; Dr. Nilanjana Chattopadhyay; Dr. Chintamoni Nayak; Dr. Anamitra Chattopadhyay (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Psoriasis is a chronic immune-mediated papulosquamous inflammatory skin condition. A case of 45 years’ male came to OPD with complaint of psoriasis for last 20 years. Psorinum had a significant importance in the management of chronic psoriasis on the basis of similimum. As per response of medicine on patient for recurring follow up of 5-6 months, he was showing remarkable relief in his condition, he started improving on his next follow-up visits and now he is free from his disease. This article manifests the utility of homoeopathic medicine Psorinum in management of cases of psoriasis.